Validation of thin layer drying models in solar-powered air-inflated grain dryer - DUBEY, ABHINAV; SHARMA, P K; MANI, INDRA; PARRAY, ROAF AHMAD; ARADWAD, PRAMOD; T V, ARUN KUMAR (The Indian Journal of Agricultural Sciences, 2021)
Cereals are generally harvested at 20-23% moisture content to avoid shattering losses therefore it is necessary to dry the paddy to lower moisture contents (13-14% wb) for safe storage and further processing.A solar-powered airinflated grain dryer was designed, fabricated and tested for drying of paddy. Different combinations obtained from two different levels of upper transparent polyethylene sheet thickness (200 microns and 300 microns), inlet air velocity (1.5 m/s and 3 m/s) and grain bed depth (2cm and 4cm) were compared based on parameters of thermal efficiency, rise in temperature of drying air and amount of moisture removed per unit time. It was found that least square mean values of thermal efficiency, temperature rise in the drying air and drying rate of the developed dryer varied from 18.7-45.7%, 3.35-5.81Â°C and 0.36-0.98 kg/hour respectively. Upper transparent sheet thickness (300 micron), inlet air velocity (3 m/s) and grain bed depth (4 cm) have the highest least mean square values in the selected parameters and was selected for optimized operation of the dryer. Eight different thin layer drying models were compared according to their coefficient of determination to estimate drying kinetics as criteria for evaluating the goodness-of-fit. The effects of selected variables on the model constants and coefficients were predicted by the models. The page model fit well with the experimental data and satisfactorily describe the drying kinetics of Pusa Basmati (PB 1121) with a coefficient of determination (R2) of 0.9995 and RMSE of 0.005464.